THE INFLUENCE OF ANDROID-BASED EDUCATIONAL GAME MEDIA ON COGNITIVE AND PSYCHOMOTORIC STUDENTS AGED 4-5 YEARS OF KINDERGARTEN PERTIWI MAYANG JEMBER - Karunia Muda Setya Utama (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This research is causal quantitative research that wants to determine the effect of android-based educational games on cognitive and psychomotor for students aged 4-5 years at TK Pertiwi Mayang even semester of the 2019-2020 academic year. The problems studied in this problem are? Is there and to what extent is the influence of Android-based educational game learning media on the cognitive enhancement of students aged 4-5 years at Kindergarten Pertiwi Mayang? The research design used by the researcher is quantitative with the causal method. Analysis of the data used is multiple correlation. From the results of multiple correlation test analysis using the SPSS v.22 for Windows application. Obtained the value of Sig. (2-tailed) <0.05 that is 0.00 <0.05. It can be concluded that Ho is rejected and Ha is accepted. So that there is an effect of Android-based educational games on cognitive and psychomotor for children aged 4-5 years at Pertiwi Mayang Kindergarten. Suggestions addressed to several parties in order to increase student interest in learning for the future are as follows: 1) In particular, the headmaster of Kindergarten Pertiwi Mayang can take advantage of the available time to provide competency development to teachers or educators to carry out their roles and duties as educators by even better for the achievement of educational goals as expected. In addition, the principal must also take the time to just look, moreover, it can provide motivation for his students. 2) The teacher councils so as not to get bored guiding, teaching, and achieving creative, innovative, and fun learning breakthroughs in order to carry out a good and optimal learning process so as to generate a better sense of student confidence. 3) Parents should give more space or time to their children to express themselves in order to support children's character development so that it can be even better. Furthermore, parents must be more active in monitoring and motivating their children to explore better potential than before.